Simulation of the influence of intrinsic C-S-H aging on time-dependent relaxation of hydrating cement paste. (30th December 2017) - Li, X.; Grasley, Z.C.; Garboczi, E.J.; Bullard, J.W.
Highlights: Computational model probed effect of C-S-H creep on cement paste relaxation. If aging is ignored, model shows C-S-H creep induces greater creep of older cement paste. With significant aging, C-S-H creep can be a viable mechanism for cement paste creep. Abstract: The viscoelastic/viscoplastic behavior of cement paste may occur due to intrinsic calcium silicate hydrate (C-S-H) viscoelasticity/viscoplasticity and cement grain dissolution during the hydration process. A numerical model that combines a microstructure model and a finite element calculation model has been developed to predict the time-dependent behavior of cementitious materials based on these two mechanisms, while incorporating C-S-H intrinsic aging. The simulation results from the model suggest that when considering C-S-H aging, the time-dependent properties of C-S-H are capable of generating the aging effect of cement paste, and can become a significant mechanism leading to the overall relaxation of cement paste.